Transformation of Meaning Based on Cultural Context in the Translation of Lontar Yusuf into Indonesian - Umu Nafisatul Munawaroh1; Hasan Busri; Sri Wahyuni (Universitas Negeri Semarang, 2026)
This study aims to analyze the transformation of cultural meaning in the translation of Lontar Yusuf into Indonesian to understand the changes in meaning that occur in the process of translating traditional texts rich in cultural and religious values. The research data were sourced from Lontar Yusuf Banyuwangi: Pegon Text–Transliteration–Translation and analyzed using an interpretive qualitative approach with a bounded-corpus design. The data were purposively selected based on indications of cultural significance transformations in the source and target texts. Data analysis is carried out through thematic analysis, which includes coding, category grouping, and theme interpretation, and is supported by comparing meaning components to identify the forms of meaning change that occur. The results of the study show that there are four forms of cultural meaning transformation, namely narrowing meaning, expanding meaning, generalization, and shifting spiritual meaning. The findings also show that translation strategies oriented towards the target culture are more prevalent than strategies that preserve elements of the source culture, resulting in a simplification of the representation of cultural and spiritual meaning in the translated text. This research contributes to the study of traditional text translation by deepening understanding of the transformation of cultural meaning in translation and its implications for the preservation of cultural and religious values in target texts.